ADP-glucose pyrophosphorylase is activated by posttranslational redox-modification in response to light and to sugars in leaves of Arabidopsis and other plant species - Hendriks, J.H.M; Kolbe, A; Gibon, Y; Stitt, M; Geigenberger, P (Plant physiology (Bethesda), 2003)
ADP-glucose pyrophosphorylase (AGPase) catalyzes the first committed reaction in the pathway of starch synthesis. It was recently shown that potato (Solanum tuberosum) tuber AGPase is subject to redox-dependent posttranslational regulation, involving formation of an intermolecular Cys bridge between the two catalytic subunits (AGPB) of the heterotetrameric holoenzyme (A. Tiessen, J.H.M. Hendriks, M. Stitt, A. Branscheid, Y. Gibon, E.M. Farre, P. Geigenberger [2002] Plant Cell 14: 2191-2213). We show here that AGPase is also subject to posttranslational regulation in leaves of pea (Pisum sativum), potato, and Arabidopsis. Conversion is accompanied by an increase in activity, which involves changes in the kinetic properties. Light and sugars act as inputs to trigger posttranslational regulation of AGPase in leaves. AGPB is rapidly converted from a dimer to a monomer when isolated chloroplasts are illuminated and from a monomer to a dimer when preilluminated leaves are darkened. AGPB is converted from a dimer to monomer when sucrose is supplied to leaves via the petiole in the dark. Conversion to monomeric form increases during the day as leaf sugars increase. This is enhanced in the starchless phosphoglucomutase mutant, which has higher sugar levels than wild-type Columbia-0. The extent of AGPB monomerization correlates with leaf sugar levels, and at a given sugar content, is higher in the light than the dark. This novel posttranslational regulation mechanism will allow starch synthesis to be regulated in response to light and sugar levels in the leaf. It complements the well-characterized regulation network that coordinates fluxes of metabolites with the recycling of phosphate during photosynthetic carbon fixation and sucrose synthesis.